Investment and Military-Technical Cooperation of Ukraine with Azerbaijani Republic: The Current State and Prospects - O. M. Motuzka; N. A. Hrynchak; A. G. Tarasenko (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2019)
The analysis of investment cooperation between Azerbaijani Republic and Ukraine shows a positive trend from 2014 and on. As of December 31, 2017, the Ukrainian economy attracted investment of 213 million USD from Azerbaijan. The main sectors of Azerbaijani investment in Ukrainian are wholesale and retail trade, repair of motor vehicles, construction and industry. Direct investment of Ukraine to Azerbaijan in 2017 amounted to 25 million USD.The clear position of the Azerbaijani government in terms of facilitating business conditions can help attract Ukrainian investment and Ukrainian business to cooperate with Azerbaijani companies. Comfortable taxation, the termination of two years of inspections of business entities, the possibility of obtaining financing: all this increases the attractiveness of investment in small and medium businesses in Azerbaijan and makes the country attractive for foreign business.The study shows that the current state of military-technical cooperation is not in the best condition, but it has significant potential for development. In this regard, the promising area of military-technical cooperation between Azerbaijani Republic and Ukraine is the transfer of Ukrainian experiences in the production of light-weight wheeled vehicles such as APCs, radar detection of air targets, and anti-personnel combat weapons. Most importantly, all of this technique will be more competitive in terms of price compared with Western counterparts and with the already existing experience of counteracting the latest Russian technology and technologies (which are actively used in the Donbass).A promising area of cooperation may be the transfer of experiences in the modernization of anti-aircraft missile systems of Soviet production. This problem is now very actively engaged in our country at the state level and there are already real results. For example, Ukrainian companies were able to master the repair and modernization of missiles for such anti-aircraft missile systems as the S-300 (including modifications B1), Osa-AKM, and Cub-M1. There are good variants of modernization of missiles for the complex С-125, which is being armed with air defense of Azerbaijan.